2015
DOI: 10.1016/j.jvs.2014.04.078
|View full text |Cite
|
Sign up to set email alerts
|

Mortality variability after endovascular versus open abdominal aortic aneurysm repair in a large tertiary vascular center using a Medicare-derived risk prediction model

Abstract: Despite treating patients with high preoperative risk status, we report a 10-fold decrease in operative mortality for EVAR and open AAA repair in a tertiary vascular center compared with national Medicare-derived predictions. High-risk patients should be considered for aneurysm management in dedicated aortic centers, regardless of approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Some 3061 articles were identified, of which 115 were selected and read in full. Eventually 53 studies fulfilled the inclusion criteria ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
“…Some 3061 articles were identified, of which 115 were selected and read in full. Eventually 53 studies fulfilled the inclusion criteria ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies have assessed the association between postoperative AKI and mortality in patients undergoing AAA repair. 5,[9][10][11] The 30-day mortality rates after AAA repair were higher in octogenarians compared with nonoctogenarians, especially in those undergoing OAR (OAR, 5.7% vs 1.7%; EVAR, 1.5% vs 0.5%). These findings are in line with those reported in previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…5 Nevertheless, postoperative renal impairment is associated with increased morbidity and mortality, in both OAR and EVAR. [8][9][10][11] Age is an established risk factor for mortality after AAA repair. 12 Elderly patients, aged 75 years and above, have been found to perform worse and have more postoperative complications than their younger counterparts after AAA repair.…”
mentioning
confidence: 99%
“…Our prior studies involving infrarenal and TAA aneurysms have also reported similar results to our current study involving juxtarenal, pararenal, and suprarenal aneurysms. [17][18][19][20][21][22][23][24] These benefits with the endovascular approach are largely due to the absence of aortic cross-clamping above renal and mesenteric vessels, that is physiologically demanding and leads to increased hemodynamic cardiac stress and end-organ ischemia. Additionally, compared to endovascular repair, patients undergoing OAR also had increased length of hospital stay and were more likely to return to operation room.…”
Section: Discussionmentioning
confidence: 99%